An interactive fuzzy approach for solving multi product, multi period production planning problem - Seyed Hossein Razavi Hajiagha; Hadi Akrami; Shide Sadat Hashemi (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2014)
Master production scheduling is a midterm phase in planning which translates the long term aggregate production planning to a plan which determines the scheduling and magnitude of different products production. This problem requires investigating a wide range of parameters about demand, manufacturing resource usage and costs. Uncertainty is an intrinsic characteristic of these parameters. In this paper, a model is developed for master production scheduling under uncertainty where demands are considered as stochastic variables, while cost and utilization parameters are expressed as fuzzy numbers. A hybrid approach is also proposed to solve the extended model. The application of the proposed method is examined in a numerical example.